Silver nanoparticles induced hippocampal neuronal damage involved in mitophagy, mitochondrial biogenesis and synaptic degeneration. (August 2022) - Chang, Xiaoru; Niu, Shuyan; Shang, Mengting; Li, Jiangyan; Zhang, Wenli; Sun, Zuoyi; Li, Yunjing; Wu, Tianshu; Zhang, Ting; Tang, Meng; Xue, Yuying
Abstract: Silver nanoparticles (AgNPs) could accumulate in the central nervous system (CNS) and induce neurotoxicity for their widespread use in industry and medicine. Mitochondria are vulnerable to toxicity of AgNPs, however, their role in the neurotoxicity remains unclear. This study aimed to evaluate AgNPs-induced synaptic degeneration in mouse hippocampal neurons (at a dose of 12–120 mg/kg BW via intravenous injection), and to further investigate mechanism of mitophagy, mitochondrial biogenesis process in the neurotoxicity. The results indicated that AgNPs accumulated in mouse hippocampal neurons and induced neurological deficits of learning and memory, which involved in synaptic degeneration accompanied with mitochondrial damage. Mechanistically, AgNPs exposure increased protein expression of PTEN-induced kinase 1 (PINK1), Parkin and inhibited peroxisome proliferator-activated receptor coactivator 1 alpha (PGC-1 α ) protein expression, caused disturbed mitophagy and mitochondrial biogenesis. AgNPs also induced synaptic damage by increasing the protein expression of synaptophysin and decreasing PSD95, MAP2 protein expression. AgNPs exposure even promoted protein expression of amyloid precursor protein (APP) using in amyloid- β (A β ) cleavage. Furthermore, AgNPs induced hippocampal neuronal synaptic degeneration, mitophagy and mitochondrial biogenesis is dependent on particle-specific AgNPs rather than released silver ions. Our research could provide insights into the regulatory mechanisms of AgNPs-induced neurotoxicity. This study will shed the light of neurotoxicological evaluation of nanoparticles and possible early warning of biomedical applications. Graphical abstract: Image 1